PP.40.20: NEW EVALUATION APPROACH OF PHARMACOLOGICAL ADHERENCE OF RESISTANCE HYPERTENSION PATIENTS. (June 2015) - Corrêa, N.; Ritter, A.M.; Faria, A.P.; Fontana, V.; Barbaro, N.; Sabbatini, A.; Brunelli, V.; Modolo, R.; Moreno, H.
Abstract : Objective: The resistant hypertension (RHTN) is defined by blood pressure (BP) above 140 / 90mmHg, despite the use of 3 or more antihypertensive agents of different classes, including if possible a diuretic. Some hypertensive patients are falsely categorized as RHTN due to non-adherence to pharmacological therapy. Therefore, it is essential the evaluation of adherence with a reliable method in this group of patients. However, an ideal method for this purpose is unknown. The triamterene emerges as a potential biochemical marker of pharmacological adherence. The objective of this work is the assessment of the adherence to pharmacological treatment by direct method in RHTN subjects. Design and method: A pilot test was conducted with twelve volunteers: nine normotensives and three mild to moderate hypertensives. A serial collection of urine was performed before and after administration of triamterene, until the 12-hour period. The ROC curve was used to determine the fluorescence cutoff value of triamterene in the urine. In addition, the evaluation of adherence in the RHTN patients (n = 21) was performed in three home visits by collecting urine. The adherent patients should have the minimum fluorescence detected in all 3 visits. Results: The patients that administered triamterene showed a significant increase in the fluorescence values throughout the study period, as opposed to those who did not take the medication. A fluorescence peak was observed up to 6 hours, and therefore, this time was considered the ideal for analysis. In ROC curve analysis, patients were considered adherents when the fluorescence was above 0.44 x105. Among the 21 RHTN subjects evaluated, 9 patients were considered adherents and 12 non-adherents. Conclusions: The fluorescence analysis of triamterene in urine may be considered a potential method of evaluation of drug adherence in patients with resistant hypertension.